"Everybody's hard times are different": country as a political investment in white masculine precarity. Issue 2 (3rd April 2019) - Edgar, Amanda Nell; Holladay, Holly Willson
ABSTRACT: Recognizing the complex interplay between country music, lifestyle, and identity, and the disparate nature of these texts and their producers, we center our analysis of the politics of contemporary "country" in the accounts of country music listeners. Through this lens, "country" foregrounds a portrait of precarious labor and white rural economies. Precarity is held up as aspirational, facilitated by the relative structural support of whiteness and masculinity that simultaneously leverages economic hardship to obfuscate these privileged positions. "Country" elides experiences of class marginalization, white rurality, and masculinized labor with mythologized narratives that position simplicity and work as "the good life."